Investigation of the precipitation of Na2SO4 in supercritical water. (31st December 2017) - Voisin, T.; Erriguible, A.; Philippot, G.; Ballenghien, D.; Mateos, D.; Cansell, F.; Iversen, B.B.; Aymonier, C.
Graphical abstract: Highlights: Salt precipitation issue in SCWO process with Na2 SO4 as model salt. Continuous experimental set-up for measuring on line salt solubility. In situ determination of crystallite sizes. Numerical modeling of salt precipitation coupling CFD and population balance equation. Abstract: SuperCritical Water Oxidation process (SCWO) is a promising technology for treating toxic and/or complex chemical wastes with very good efficiency. Above its critical point (374 °C, 22.1 MPa), water exhibits particular properties and organic compounds can be easily dissolved and degraded with the addition of oxidizing agents. But these interesting properties imply a main drawback regarding inorganic compounds. Highly soluble at ambient temperature in water, these inorganics (such as salts) are no longer soluble in supercritical water and precipitate into solids, creating plugs in SCWO processes. Although this precipitation phenomenon is well known as a limiting factor for SCWO process, it is still not well understood. This work intends to investigate the precipitation phenomenon with a new methodology. A common salt, disodium sulfate (Na2 SO4 ), is taken as a reference for the study. Na2 SO4 solubility in sub- and supercritical water is determined on a wide temperature range using a continuous set-up. Crystallite sizes formed after precipitation are measured with in situ synchrotron wide angle X-ray scattering (WAXS). Combining these experimental results, a numerical modeling of the precipitation in supercritical conditions is performed by taking into account all the implied physical phenomena: thermodynamic, hydrodynamic and nucleation & growth.